THE EFFECT OF FERMENTED TARO FRONDS (Colocasia esculenta) ON THE GROWTH PERFORMANCE AND SURVIVAL RATE OF MILKFISH (Chanos chanos) - Seo, Angli Y. Y.; Salosso, Yuliana; Djonu, Asriati (Journal of Aquaculture Development and Environment, 2024)
Taro fronds (Colocasia esculenta) are a natural ingredient that is abundantly available with sufficient nutritional content to be used as a feed ingredient. The research aims to determine the effect of fermented taro fronds (C. esculenta) on the growth and survival rate of milkfish (Chanos chanos) which was carried out at the Oesapa Pond Hatchery Unit. Milkfish (C. chanos) were distributed to experimental units according to procedures using a Completely Randomized Design (CRD) with four treatments and three replications. The treatments tested included Control (100% commercial feed), P1 (addition of 5% fermented taro fronds), P2 (8% addition of fermented taro fronds) and P3 (10% addition of fermented taro fronds). The results of the study showed that there had been an increase in absolute growth of 20.93 g, survival rate of 100% and a specific growth rate of 2.23% g/day. However, ANOVA showed that treatment had no significant effect on absolute weight, survival rate ratemand specific growth rate.